Speak 20th anniversary edition. - Anderson, Laurie Halse; Siegfried, Mandy (New York : Listening Library, 2006)
"Speak up for yourself―we want to know what you have to say." From the first moment of her freshman year at Merryweather High, Melinda knows this is a big fat lie, part of the nonsense of high school. She is friendless, outcast, because she busted an end-of-summer party by calling the cops, so now nobody will talk to her, let alone listen to her. As time passes, she becomes increasingly isolated and practically stops talking altogether. Only her art class offers any solace, and it is through her work on an art project that she is finally able to face what really happened at that terrible party: she was raped by an upperclassman, a guy who still attends Merryweather and is still a threat to her. Her healing process has just begun when she has another violent encounter with him. But this time Melinda fights back, refuses to be silent, and thereby achieves a measure of vindication. A timeless novel about consent and finding the courage to speak up for yourself, the twentieth anniversary edition of the classic novel that has spoken to so many young adults now includes a new introduction written and read by acclaimed writer, host, speaker, and cultural commentator Ashley C. Ford as well as an afterword written and read by New York Times- bestselling author of All American Boys and Long Way Down, Jason Reynolds. This edition will also feature an updated Q&A, resource list, and essay and poem written and read by Laurie Halse Anderson. Praise for Speak : “In a stunning first novel, Anderson uses keen observations and vivid imagery to pull readers into the head of an isolated teenager. . . . Will leave readers touched and inspired .” ― Publishers Weekly , starred review “An uncannily funny book even as it plumbs the darkness, Speak will hold readers from first word to last.” ― The Horn Book , starred review Accolades for Speak : New York Times Bestseller Publishers Weekly Bestseller Michael L. Printz Honor Book National Book Award Finalist Edgar Allan Poe Award Finalist Los Angeles Times Book Prize Finalist ALA Top Ten Best Book for Young Adults ALA Quick Pick Publishers Weekly Best Book of the Year Booklist Top Ten First Novel BCCB Blue Ribbon Book School Library Journal Best Book of the Year
Unabridged.
Narrator: Mandy Siegfried.
Text Difficulty 3
UG/Upper grades (9th-12)
690
4.5
Keywords: Young Adult Fiction; Young Adult Literature; Electronic books